Potret Praktik Akuntansi oleh Pengusaha Kos-kosan berbasis Nilai Budaya Lokal - Thalib, Mohamad Anwar; Kuntuamas, Muhliansyah J.A; Umar, Tiara Pratiwi A; Sulastri, Ririn Dwi (Penerbit Goodwood, 2023)
Purpose: This research aims to photograph accounting practices of boarding house entrepreneurs based on local cultural values. Methodology/Approach: This study uses a spiritual paradigm with an Islamic ethno-methodology approach. There are five stages of data analysis: charity, knowledge, faith, revealed information, and ihsan. Qualitative methods were used. Data collection techniques consisted of passive participant observation and structured interviews. Purposive sampling was used to determine informants. The participants were three boarding-house entrepreneurs. Results: The research results show capital accounting practices and simple capital-recording methods. In addition, boarding-house entrepreneurs practice accounting based on the value of worship. This is reflected in the actions of boarding house entrepreneurs, who use profits from boarding house businesses not only for worldly interests but also for the interests of the afterlife, such as sharing with people in need and carrying out the Umrah pilgrimage. Incorporating worship in all activities is one of the local communities’ local cultural values, which is often expressed through lumadu